A clinical case of infectious mononucleosis combined etiology (EBV + CMV) on the background of aplastic anemia in a teenager - E. B. Pavlova; D. O. Ivanov; V. N. Timchenko; N. V. Pavlova; A. N. Nazarova; G. V. Kondratiev; T. M. Chernova; A. V. Fedorova; A. A. Danilina; O. V. Bulina (LLC "Diagnostics and Vaccines", 2023)
Infectious mononucleosis of various etiologies occupies one of the leading places in the structure of childhood infectious diseases. It is known that after suffering Epstein-Barr infectious mononucleosis of viral or cytomegalovirus etiology, there is a risk of agranulocytosis, and aplastic anemia with pancytopenia may occur. The combination of two viruses in the etiology of infectious mononucleosis is usually accompanied by severe forms of the disease and a high risk of complications. A clinical case of a severe form of infectious mononucleosis of combined etiology against the background of aplastic anemia (AA) in a teenager aged 15 years and 9 months is presented. The high risk of developing septic complications in AA during the height of MI was the basis for the abolition of cyclosporine, the main treatment for aplastic anemia in a patient. The use of complex therapy, including etiotropic agents, transfusions of donor blood components, intravenous immunoglobulins, made it possible to stabilize the patient's condition for infectious mononucleosis and achieve positive dynamics. At the same time, decompensation of the state according to AA against the background of an acute infection required further treatment of the patient in a specialized hematological hospital.